(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article discusses the question of what is the essence of evidence in criminal cases. The relationship between the concepts “any information” and “factual data” is analyzed in order to define the concept of evidence in criminal cases. The purpose of using evidence in criminal cases is based. It follows from this that it is necessary to justify all procedural decisions with reasonable and admissible evidence.